A new Afromontane species of the ant-eating spider genus Dusmadiores and description of the male of D. deserticola (Araneae: Zodariidae) - Vanderhaegen, Koen; Jocqué, Rudy (Zootaxa, 2017)
Dusmadiores elgonensis sp. nov. (♂♀) is described from the Mount Elgon region, Uganda. It is the first Dusmadiores species found within the eastern Afromontane highlands. D. elgonensis is remarkable by the presence of a conspicuous group of spines on the retrolateral side of the cymbium just in front of the RTA in males. The unknown male of D. deserticola Jocqué, 2011 is described. The type locality of the latter species is corrected to Cabo Verde, Santiago, São Jorge dos Órgãos. An illustrated key to the seven known Dusmadiores species is provided.